Angel’s Redemption in Francine Rivers’ Redeeming Love - Debora Irwanto; Jenny M. Djundjung (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This article deals with the main female character, Angel’s, redemption in the Christian Romance novel, Redeeming Love. This article will discuss Angel’s perception of her body before her marriage and how that perception changes after her marriage to Michael. To analyze Angel’s concept of her body, I will use biblical verses in the books of Genesis, Corinthian, John, and Luke. I find that Angel regards her body as an empty vessel before her marriage to Michael. By finding Angel’s perspective of her body before her marriage, I found that Angel uses her body and soul separation as a strategy to deal with her pain. Once she is married, Angel regards her body as the temple of God and uses her knowledge of her body as the temple of God to help others like her receive God. At last, I can conclude that the Christian romance genre can be used as tool to spread the Christian perspective about the body.